Benefits of battery hybridization in hydraulic turbines. Wear and tear evaluation in a Kaplan prototype. (November 2022) - Valentín, David; Presas, Alexandre; Egusquiza, Mònica; Drommi, Jean-Louis; Valero, Carme
Abstract: Kaplan turbines are nowadays used to provide Frequency Containment Reserve (FCR) to the grid due to their fast capacity to regulate their power maintaining high efficiency. However, this continuous power regulation increases the wear and tear of the regulation system considerably. To reduce the amount of movements in the regulation servomotors, and thus their wear and tear, a new technology is being investigated within the frame of the European project XFLEX Hydro. This new technology is based on hybridizing the hydro unit with a small size battery in parallel, this one being in charge of compensating the small frequency fluctuations in the grid by providing or absorbing power. In this paper, the benefits of the implementation of this new technology are evaluated. A Kaplan turbine prototype located in Vogelgrun, France, has been hybridized and different parameters have been monitored while the unit was working in hybrid mode and in normal standalone hydro mode. Wear and tear of the regulation system have been compared for both hybrid and standalone hydro modes. A reduction of about 25% in servomotors mileage and of 50% in fatigue damage have been obtained by hybridizing the unit. Highlights: Benefits of hybridizing hydro units with a battery are studied. A small size battery is installed in parallel with a prototype Kaplan unit. The battery helps to provide primary frequency control reducing the wear and tear of the hydro unit. A reduction of wear and tear in the hydro unit regulating systems is obtained.